Manhaj al-naqd al-adabi `inda Ibn Rashiq fi kitabihi "Al-`Umdah" / Animashahun Ma`ruf Suraqat. - Animashaun, Ma‘ruf Suraqat (2012)
This research attempts to study literary criticism and Arabic poetic theory by focusing on Ibn Rashiq al-Qayrawani (390 - 456 A.H / 1000 – 1064 C.E.) al’Umda, a literary treatise of Medieval Arabic scholarship. This research work will be focusing on: Ibn Rashiq’s treatise “al-‘Umda”, the Pillar in the poetic craft, its etiquette, and criticism. This research, while utilizing historical, descriptive and inductive methods of approach, is essentially analytical, and thereby attempts to unlock the door to the literary, artistic and aesthetic treasures of his lyrics. The study opens with a re-survey of history of the Arab West, most importantly, the city of Qayrawan and its cultural life, wherein a lighthouse was erected, so as to throw more light on the prominent poets of the province and their poetics, as it serves as a precursor to the mainstream of our discussion on the subject matter: Ibn Rashiq al-Qayrawani, author of al-‘Umda, hence we cited his intellectual life, biography and highlighting his literary outputs, content and structure of his lyrics were subjected to critical study and artistic analysis. Arabic literary tradition, both its prose and poetic licenses, had witnessed a resounding development in these periods. This has caught the attention of the researcher to have a bird eye view and as well, a rethink to delve into the book “Al-Umda” so as to fill a vacuum in the study of literary criticism and most especially on Arabic poetics. The research is based on two methods: inductive and analytical, suffice it to say that, the study has proved that literary criticism of these periods (Medieval) has reached a culmination in the hands of poetic critics and prominent poets of the periods. The study also describes some important aspects of literary themes, most especially, issues regarding literary plagiarism, word and content (meaning), the moderns and the ancients. These literary themes were distinguished by artistic and structural features in the embellishment of words, such as expression of meaning, imagination, and literary imagery that are encompassed in this study.